Empowering MSMEs Through Strengthening Business Legality In Marga Sungsang Village, Banyuasin II District, Banyuasin District - Dian Novita Fajar Sari (Abdimas Paspama, 2024)
The government is committed to empowering Usaha Mikro Kecil dan Menengah (UMKM) in Indonesia, because UMKM are one of the driving forces of economic. Through UMKM, they can contribute to absorbing labor. In order for UMKM to compete in the global market era, UMKM must be strengthened by the ownership of business license legality (NIB) because it is a standard that must be met by business actors. UMKM in Cogreg village generally understand the importance of the legality of business licenses and marketing strategies because they can increase production. Through seminar activities on the importance of business license legality for UMKM, and marketing strategy assistance provided to UMKM actors in accordance with the needs of Cogreg village business actors. The benefits obtained through seminars and mentoring programs for UMKM actors are that UMKM actors are aware of the importance of having business legality and time effectiveness because it minimizes costs for distribution.